Estudio técnico - económico para la implementación de un servicio de transporte inclusivo para las personas con discapacidad en la parroquia San Camilo, cantón Quevedo, año 2015 - Salvatierra Silva, Vivianna Beatriz (2015)
This project is focused on creating an inclusive transportation services for people with disabilities in the St. Camillus parish Quevedo canton, for it is necessary to know the transportation needs of each client according to their disability. For the implementation of inclusive transport service for the disabled, it was necessary to develop the necessary steps for the implementation of the project as market segment focused on people with disabilities, technical aspects of vehicles, legal requirements, capacity and quantity hiring staff, logistics operation. To develop the above requirements investigation mobilization needs of people with disabilities through surveys and interviews was implemented. Which resulted that disabled people need a way suited to their needs transportation to improve their mobility, because although there are different ways to provide a service of transportation both comply with the conditions and do not meet their real needs. A technical economic analysis, which will allow the proper implementation of inclusive transportation services for the disabled, in which the necessary investment, seed capital, expenses, sales costs and which provide a broad overview of the economics of the project, was determined to be performed implemented. Finally, the conclusions of the research study are expressed. Keywords: People with disabilities, social inclusion, mobility, transportation, sales, economic study and technical study.